(untitled) (Cuea Journal of Business and Economics, 2025)
The financial viability of Nairobi City County's retail bookstores has been threatened by growing operating expenses, declining profit margins, and poor cash management techniques. This study evaluated the impact of cash management practices on the financial sustainability of retail bookstores in Nairobi City County. Anchored in the Free Cash Flow Theory, the study employed a cross-sectional survey design and adopted a quantitative methodology. The target population comprised 67 registered bookstores, and the study adopted a census inquiry that included all managers from these bookstores, achieving an 85 percent response rate. Primary data were collected using structured questionnaires. Descriptive statistics and simple linear regression were employed for analysis. With a 62 percent explanatory power, the findings demonstrated that financial sustainability was significantly affected by cash management strategies. The data suggests that retail bookstores strongly and positively rely on the use of cash management techniques to be financially sustainable. These findings recommend that bookstores adopt and strictly follow their cash flow planning, budgeting and monitoring processes in order to prevent liquidity crisis. The study offers the following recommendations; managers need to be more careful with the budgeting, forecasting and reconciliations of their financial reports, they need to spend the surplus cash productively and they need to undergo consistent training so that they can improve their financial management abilities. It is also greatly recommended that policymakers and business organizations should offer advisory services and interventions to the industry to support it